Interactions Between Levels of Methionine and Lysine in Broiler Diets Changed at Typical Industry Intervals - Cafe, Marcos B.; Waldroup, Park W. (International Journal of Poultry Science, 2006)
This study was conducted to evaluate the use of Met and Lys levels in excess of NRC (1994) recommendations adapted to feeding periods more consistent with current industry applications. Diets were formulated to provide a minimum of 110% of NRC recommended levels for amino acids other than Met and Lys. Aliquots of the diets were fortified with DL-methionine and Lysine HCl to provide three levels of Met (100, 115 and 130% of NRC) and four levels of Lys (100, 110, 120 and 130% of NRC) in a factorial arrangement. Feeding times were 1-16 d for starter, 16-35 d for grower, and 42-49 d for finisher. Eight pens of 65 male birds were fed each test diet. Birds were weighed and feed consumption determined at 16, 35, 42, and 49 d. Samples of birds were processed at 35, 42, and 49 d for parts yield. In general, responses to Met and Lys were independent with few interactions. Increasing Met above NRC recommendation improved BW only at 35 d but significantly improved feed conversion at 35, 42, and 49 d. Increasing Lys resulted in significant BW improvement at all ages with improved feed conversion at 16 and 42 d. Breast yield at 35, 42, and 49 d was significantly improved by levels of Met in excess of NRC recommendations. At 35 d breast yield was first increased and then decreased as Lys was increased above NRC. Breast yield at 42 and 49 d was not significantly influenced by dietary Lys content. The results of this study indicate that when fed at time intervals more consistent with current industry practice that Lys and Met levels are more critical than when fed at intervals on which NRC recommendations are based.